4-Sulfonatocalixarene-induced nanoparticle formation of methylimidazolium-conjugated dextrans: Utilization for drug encapsulation. (1st November 2019) - Wintgens, Véronique; Guigner, Jean-Michel; Miskolczy, Zsombor; Amiel, Catherine; Biczók, László
Highlights: Imidazolium-grafted dextrans self-assemble with sulfonatocalixarenes into nanoparticles. Spherical particle morphology and stoichiometry close to charge compensation are found. Nanoparticle diameter barely depends on macrocycle size and molecular mass of polymer. Decrease of substitution degree substantially diminishes the stability of the associates. Association efficiency of 99% can be reached with coralyne alkaloid. Abstract: Methylimidazolium side groups were grafted via ether linkage to dextran and the self-assembly of these polymers with 4-sulfonato-calix[n]arenes (SCXn) was studied in aqueous solutions. Dynamic light scattering and zeta potential measurements revealed the mixing ratio ranges of the constituents where stable nanoparticles could be created. The macrocycle size of SCXn and the molecular mass of the polymer barely affected the nanoparticle diameter, but the lowering of the imidazolium degree of substitution substantially diminished the stability of the associates. The pH change from neutral to acidic also unfavourably influenced the self-organization owing mainly to the decrease of the SCXn charge. Cryogenic transmission electron microscopy images proved the spherical morphology of the nanoproducts in which the stoichiometry of the constituents was always close to the one corresponding to charge compensation. The flexible and positively charged dextran-chains are compacted by the polyanionic SCXn. Coralyne, a pharmacologically important alkaloid was efficiently embedded by self-assembly in the produced nanoparticles reaching 99% association efficiency.